Sugar compartmentation as an environmental stress adaptation strategy in plants. (November 2018) - Yamada, Kohji; Osakabe, Yuriko
Abstract: The sessile nature of plants has driven their evolution to cope flexibly with ever-changing surrounding environments. The development of stress tolerance traits is complex, and a broad range of cellular processes are involved. Recent studies have revealed that sugar transporters contribute to environmental stress tolerance in plants, suggesting that sugar flow is dynamically fluctuated towards optimization of cellular conditions in adverse environments. Here, we highlight sugar compartmentation mediated by sugar transporters as an adaptation strategy against biotic and abiotic stresses. Competition for sugars between host plants and pathogens shapes their evolutionary arms race. Pathogens, which rely on host-derived carbon, manipulate plant sugar transporters to access sugars easily, while plants sequester sugars from pathogens by enhancing sugar uptake activity. Furthermore, we discuss pathogen tactics to circumvent sugar competition with host plants. Sugar transporters also play a role in abiotic stress tolerance. Exposure to abiotic stresses such as cold or drought stress induces sugar accumulation in various plants. We also discuss how plants allocate sugars under such conditions. Collectively, these findings are relevant to basic plant biology as well as potential applications in agriculture, and provide opportunities to improve crop yield for a growing population.